Environmental Benefit Assessment of Pollution and Carbon Reduction from Urban Domestic Wastewater Treatment in Guangdong Province - WANG Simiao; CHEN Deye; WANG Zixiong; FAN Yuxin; YAN Chao; WANG Tianxiang (Renmin Zhujiang)
Although urban domestic wastewater treatment reduces pollutant emissions, the greenhouse gas emissions generated during this period also force us to re-evaluate the environmental benefits of pollution and carbon reduction. Based on the IPCC inventory method and the full life cycle method, this paper constructs a carbon-pollution accounting model for urban domestic wastewater treatment and comprehensively evaluates the pollution reduction benefits and greenhouse gas emissions during the treatment period in Guangdong Province. The results show that over the past 20 years, the urban wastewater treatment rate in Guangdong Province has increased by 3.22 times, and the reduction in COD, total nitrogen, and total phosphorus has increased nearly tenfold, which has effectively reduced the environmental pollution load, contributing to the improvement of the water environment in Guangdong Province. However, wastewater treatment has generated fivefold greenhouse gas (GHG) emissions, becoming a significant source. Additionally, the intensity of GHG emissions has decreased by about 50%, and the indirect GHG reduction benefits from pollutant reduction have increased by about 1.8 times. These findings imply that the improvement of facilities can help urban domestic wastewater treatment yield more environmental benefits. It is recommended to enhance the use of clean energy and carbon recovery to improve the synergistic control capability of GHG and pollution emissions in the future.